(untitled) (Global Conference on Multidisciplinary Research and Innovation, 2026)
This article analyzes the role of digital platforms in managing service quality in the service sector. In the digital economy, improving service quality indicators in service enterprises is of great importance in ensuring customer satisfaction and strengthening the competitiveness of enterprises. The research studied the impact of CRM systems, mobile applications, online service platforms, and data analysis technologies on service processes. Also, the main directions of organizing service quality monitoring and improving service efficiency based on digital platforms were analyzed. The research results showed that the effective use of digital platforms in service enterprises contributes to improving service quality and economic efficiency.